Enzymatic Activities of CYP3A4 Allelic Variants on Quinine 3-Hydroxylation In Vitro - Zhou, Xiao-Yang; Hu, Xiao-Xia; Wang, Chen-Chen; Lu, Xiang-Ran; Chen, Zhe; Liu, Qian; Hu, Guo-Xin; Cai, Jian-Ping (Frontiers in Pharmacology, 2019)
Cytochrome P450 3A4 (CYP3A4) enzyme activity is known to show considerable ethnic heterogeneity and inter-individual differences, affecting the outcome of drug treatment. CYP3A4 genetic polymorphisms are believed to one of the important causes, leading to inter-individual variability in drug metabolism. Quinine is an antipyretic drug with antimalarial properties that is metabolized primarily by CYP3A4. Quinine 3-hydroxylation has been proven as a biomarker reaction for evaluating CYP3A4 ability. Quinine has frequent adverse effects and there are distinct inter-individual differences in quinine sensitivity. The ORF for 30 CYP3A4 allelic variants were constructed from wild-type CYP3A4*1A by an overlap extension polymerase chain reaction. Recombinant CYP3A4 variants were highly expressed using Baculovirus-Insect Cell Expression System, and their catalytic activities towards quinine hydroxylation were determined and evaluated. Most recombinant CYP3A4 variants exhibited significantly reduced Vmax and increased apparent Km, and so decreased intrinsic clearance towards quinine, compared with CYP3A4*1A. Our assessment on the enzymatic activities of CYP3A4 variants towards quinine may contribute to laying an experimental foundation for further clinical studies so as to accelerate the process of determining the associations between genetic variations and clinical phenotypes.